Baba nangko - Bettison, Joan (Cengage Learning Australia New Zeland, 1994)
Baba Nangko is a heartwarming children's story that follows the adventures of a wise and kind elder known as Baba Nangko, who is beloved in his community for his storytelling and gentle guidance. Through enchanting tales and engaging lessons, Baba Nangko imparts valuable morals about kindness, bravery, and friendship to the children around him. The narrative is rich with cultural elements and beautifully illustrated, making it a delightful read for young audiences. This charming book encourages children to embrace their imaginations while fostering a sense of community and understanding of traditional values.